Tensions between knowledge transmission and student-focused teaching approaches to assessment purposes: helping students improve through transmission. Issue 3 (2nd April 2016) - Chen, Junjun; Brown, Gavin T.L.
Abstract : This study surveyed 1064 Chinese school teachers' approaches to teaching and conceptions of assessment, and examined their inter-relationship using confirmatory factor analysis and structural equation modeling. Three approaches to teaching (i.e. Knowledge Transmission, Student-Focused, and Examination Preparation) and six conceptions of assessment (i.e. Student Development, Teaching Improvement, Examination, Control, School Accountability, and Irrelevance) were identified. Teachers indicated they used Student-Focused most frequently and this positively predicted the assessment purposes of Student Development and Teaching Improvement, while loading negatively on Control, School Accountability, and Irrelevance. The Knowledge Transmission teaching approach, in contrast, positively predicted the assessment purposes of Examination, School Accountability, Control, Student Development, and Teaching Improvement. Thus, despite a predominantly student-focused approach to teaching, knowledge transmission was seen as a teaching approach that contributed positively to student learning. Possible explanations for this anomalous result are discussed.